Initial Cost Barrier of Ammonia Control in Central China. Issue 23 (10th December 2019) - Zheng, Mingming; Wang, Yuhang; Bao, Jianguo; Yuan, Lianxin; Zheng, Huang; Yan, Yingying; Liu, Dantong; Xie, Mingjie; Kong, Shaofei
Abstract: Ammonia control has received increasing attention as a measure to decrease particulate concentrations. Modeling analysis of observation data from central China over the period of September 2015 to August 2016 shows clear asymmetric responses of particulate pH and mass to ammonia emissions. With a change of ±80% of NH x (NH3 + NH4 + ), the corresponding ΔpH are +0.5 and −3.0, respectively, and the corresponding particulate NH4 + changes are +2.62% and −61.8%, respectively. This asymmetry implies that there is a Critical Total Ammonia Concentration, above which particulate pH and mass are insensitive to ammonia control. Analysis of the observation data suggests that the Critical Total Ammonia Concentration is −25%. The estimated cost for an NH x reduction of 25% is 140 – 320 million for Hubei province, which is the initial cost barrier before ammonia control can effectively affect particulate pH and mass in central China. This cost barrier will increase as NO x and SO2 emissions decrease. Key Points: Only after NHx reduction exceeds 25% can ammonia control effectively reduce the inorganic aerosol mass More NHx reduction will be required to reach the critical point of effective ammonia control as NOx and SO2 emissions decrease A large enough NHx reduction (60%–80%) renders concurrent reduction of NOx emissions ineffective and even the effect of SO2 emission control is reduced